Effect of incorporation of La into WO3 nanorods for improving photocatalytic activity under visible light irradiation. (November 2022) - Govindaraj, T.; Mahendran, C.; Chandrasekaran, J.; Manikandan, V.S.; Shkir, Mohd; El Sayed Massoud, Ehab; Kumar, N. Senthil; Kim, Woo Kyoung; Gedi, Sreedevi
Abstract: In this paper, a facile approach to synthesizing La-doped WO3 nanorods (NRs) via a simple hydrothermal method. The effects of doping on the photocatalytic activity of WO3 have been explained in detail. The PL spectra indicate the higher charge carrier separation in 5%La-WO3 NRs. The 5%La-doped WO3 NRs exhibits higher photodegradation efficiency of rhodamine B (RhB) dye under visible light irradiation. The degradation rate constant of 5%La-WO3 NRs is 0.02633 min −1, 2.2 times greater than WO3 . The scavenging test confirmed that the OH and O2 − radicals were involved in the photodegradation process. Furthermore, the typical catalyst exhibits excellent photostability and reusability after three consecutive tests. Highlights: Pristine WO3 and La-doped WO3 NRs were synthesized by a facile hydrothermal method. Photocatalytic removal of Rhodamine B dye was performed under visible light. 5% La-WO3 NRs catalyst shows 90% of degradation efficiency. OH and O2 − radicals were involved in the photodegradation mechanism.